2014
DOI: 10.1002/hrm.21673
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction of Employees with Disabilities: The Role of Perceived Structural Flexibility

Abstract: With this article we contribute to the inclusion of employees with disabilities in the workplace. Based on Stone and Colella's (1996) model of factors affecting the treatment of employees with disabilities in organizations, we concentrate on the investigation of job satisfaction as a focal affective response. Besides examining job satisfaction differences between employees with and without disabilities, we focus on perceived flexibility as an organizational boundary condition, arguing for its influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 104 publications
1
53
0
8
Order By: Relevance
“…Primary data sources for 72% of these studies came from HR managers and employers. However, some of the largest‐scale studies in the sample also collected data from employees and persons with disabilities themselves (e.g., Baumgärtner et al, ), allowing more differentiated conclusions regarding the state and impact of organizational characteristics on the treatment of employees with disabilities.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
“…Primary data sources for 72% of these studies came from HR managers and employers. However, some of the largest‐scale studies in the sample also collected data from employees and persons with disabilities themselves (e.g., Baumgärtner et al, ), allowing more differentiated conclusions regarding the state and impact of organizational characteristics on the treatment of employees with disabilities.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
“…Thriving is especially important for PWD for two reasons. First, previous research has indicated PWD have lower levels of thriving at work because they often face increased difficulties and fewer chances to achieve full potential (Baumgärtner, Dwertmann, Boehm, & Bruch, 2015;Colella & Varma, 2001;Ren, Paetzold, & Colella, 2008;Roulstone & Gradwell, 2003;Stone & Colella, 1996;Westaby, Versenyi, & Hausmann, 2005). Roulstone and Gradwell (2003) found a considerable number of PWD in the United Kingdom were just surviving.…”
Section: Disability and Thriving At Workmentioning
confidence: 99%
“…Tras la depuración inicial de los datos, se realizaron los análisis estadísticos, para -65 -lo que se utilizó la versión 23 del paquete estadístico SPSS y el complemento AMOS. Las respuestas dadas a cada uno de los ítems del cuestionario representan una escala ordinal, por lo que para los diferentes análisis se emplearon coeficientes de correlación policóricos y para el análisis factorial exploratorio (AFE) el complemento R-Factor para este tipo de variables (Basto y Pereira, 2012). Dada la similitud de los resultados obtenidos mediante estas técnicas con los de las habituales para escala de intervalos, en aras de la interpretabilidad de los resultados presentamos los mismos considerando los valores de las variables como indicadores de una escala de intervalos.…”
Section: Análisis Estadísticosunclassified